An analysis of the mediating effects of social relations and controls on neighborhood crime victimization - Rhineberger-Dunn, Gayle M. (Western criminology review, 2011)
Recent tests of systemic social disorganization theory focus on specifying types of informal and formal controls and their ability to mediate the impact of negative structural conditions on neighborhood crime rates. However, a majority of these studies use measures that confound the quality of the relationships needed to develop both informal and formal control with the willingness to exercise these controls. We contribute to this body of literature by making a distinction between the quality of relationships that facilitate the ability to use controls (e.g., social cohesion and police-citizen relations) and the willingness to exercise informal and formal control. Specifically, we test the hypothesis that social cohesion, informal control, police-citizen relations, and formal control differentially mediate the impact that neighborhood structural characteristics have on interpersonal violence and specific types of property crime victimization. Further, we argue that the effects of informal control will be stronger than the effects of formal control, and that the impact of social cohesion and police-citizen relations will be partially mediated by their influence on the exercise of these controls. The results of our hierarchical generalized linear models show that social cohesion, informal control, police-citizen relations, and formal control differentially mediate the impact of neighborhood structural conditions on violent crime and property crime victimization. Our results suggest that strategies needed to prevent violent crime are different than those needed to prevent property crime.